The tip of the iceberg in organic chemistry classes : how do students deal with the invisible? - Graulich, Nicole; Justus Liebig University Giessen (My University, 2015)
Organic chemistry education is one of the youngest research areas among all chemistry related research efforts, and its published scholarly work has become vibrant and diverse over the last 15 years. Research on problem-solving behavior, students´ use of the arrow-pushing formalism, the investigation of students´ conceptual knowledge and their cognitive skills have shaped our understanding of college students´ understanding in organic chemistry classes. This review provides an overview of research efforts focusing on student´s perspectives and summarizes the main results and pending questions that may guide subsequent research activities.
Keywords: ddc:540